The Cardiopulmonary Effects of Medical Masks and Filtering Facepiece Respirators on Healthy Health Care Workers in the Emergency Department: A Prospective Cohort Study - DENİZBAŞI ALTINOK, ARZU; ÖZPOLAT, ÇİĞDEM; SANRI, ERKMAN; KARACABEY, SİNAN (Elsevier Inc., 2022)
Background: International COVID-19 guidelines recommend that health care workers (HCWs) wear filtering facepiece (FFP) respirators to reduce exposure risk. However, there are concerns about FFP respirators causing hypercapnia via rebreathing carbon dioxide (CO2). Most previous studies measured the physiological effects of FFP respirators on treadmills or while resting, and such measurements may not reflect the physiological changes of HCWs working in the emergency department (ED). Objective: Our aim was to evaluate the physiological and clinical impacts of FFP type II (FFP2) respirators on HCWs during 2 h of their day shift in the ED. Methods: We included emergency HCWs in this prospective cohort study. We measured end-tidal CO2 (ETCO2), mean arterial pressure (MAP), respiratory rate (RR), and heart rate values and dyspnea scores of subjects at two time points. The first measurements were carried out with medical masks while resting. Subjects then began their day shift in the ED with medical mask plus FFP2 respirator. We called subjects after 2 h for the second measurement. Results: The median age of 153 healthy volunteers was 24.0 years (interquartile range 24.0–25.0 years). Subjects’ MAP, RR, and ETCO2 values and dyspnea scores were significantly higher after 2 h. Median ETCO2 values increased from 36.4 to 38.8 mm Hg. None of the subjects had hypercapnia symptoms, hypoxia, or other adverse effects. Conclusion: We did not observe any clinical reflection of these changes in physiological values. Thus, we evaluated these changes to be clinically insignificant. We found that it is safe for healthy HCWs to wear medical masks plus FFP2 respirators during a 2-h working shift in the ED. © 2021
Keywords: COVID-19; end-tidal carbon dioxide; filtering facepiece respirators; medical masks; personal protective equipment; physiological effects